MICROSOFT FRONTPAGE 2000 APPLICATIONS IN COMPUTER HARDWARE SUPPORT INFORMATION PRESENTATION ASSEMBLY - Maifi Lino; Ir. Fitri Sjafrina. MMSi Ir. Fitri Sjafrina. MMSi (Jurnal Sistem Informasi, 2001)
Computer hardware is in great demand by the hobies and assembler, Karen canchoose their own hardware is required in accordance with the needs and abilities.However, in choosing computer hardware, the price is not always a major factor inthe quality of the computer hardware. The author tries to help by providinginformation on computer hardware that can be used as a material consideration.Based on the results of a questionnaire distributed by the author, the constraints facedtoday is the hobies and assemblers feel difficulty in choosing a motherboard andknow the price of computer hardware.Using Microsoft FrontPage 2000, the authors make a home page for information oncomputer hardware in Indonesian language. So that the hobies and assembler canview this information through the internet media.As there are several things that must be considered by the webmaster in designinghome pagedengan using Microsoft FrontPage 2000, which hit counters, search formsand guest book. We make this information, the assembler can know hobies andhardware information and the price of hardware.